Virulency of Bacillus subtilis and Trichoderma harzianum Against Sprout Disease Pythium spp. in Cucumber Plants - Minal Maimanah; Restu Rizkyta Kusuma; Luqman Qurata Aini (University of Brawijaya, 2021)
Sprout disease (damping off) is one of the important diseases that attack a variety of horticultural plants. Besides, sprouts disease can also attack seeds that have not germinated (preemergence damping-off). This study aimed to determine and compare the ability of B. subtilis and T. harzianum in controlling the pathogen Pythium spp. in cucumber plants. Phy01CK and Phy01IP isolates were use in the virulency test and inoculation methods of pathogens. The inhibition test between B. subtilis and T. harzianum against Pythium spp. was conducted in the in vitro test. This research was used a randomized block design with 13 treatments and three replications. The results of the antagonist's effect in vitro between T. harzianum and Pythium spp. showed the highest suppressing growth of Pythium spp. which is 70%. B. subtilis, B. subtilis + T. harzianum and fungicides each having a zone of inhibition of 23%, 32% and 46%. In the in vivo tests, the application of biological agents with 3 different times was not affecting the incidence of damping-off disease at 10 days after planting.